(untitled) (The New Uzbekistan Journal of Medicine, 2025)
This scientific article analyzes the main anatomical systems of the human body - skeletal, muscular, nervous, cardiovascular, respiratory, digestive, urinary and reproductive systems - morphologically and functionally. Each system is studied separately, its role in the body, its interrelationships and biological significance are considered. The skeletal and muscular systems perform the locomotor function of the body, while the cardiovascular and respiratory systems play a role in metabolism and oxygenation of tissues. The nervous system is considered as a center that provides coordinated control of all physiological processes. The digestive and urinary systems provide nutrients to the body and remove waste products. The reproductive system, along with the function of reproduction, also plays an important role in endocrine balance. The article analyzes the structure, uniqueness of each system and the importance of their study in practical medicine on a scientific basis. This article will serve as a useful scientific resource for students studying anatomy in more depth, medical professionals, and biomedical researchers.